Real Fictions: Collage, Photo Manipulation, and Architectural Image in the Digital Era - Lus Arana, Luis Miguel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2017)
Since the earliest daguerreotypes appeared in the second half of the 19th century, the manipulation of photographic image has been an inseparable companion of the development of the medium. Firstly introduced as a way to make up for the limitations of technique, soon they started being used as privileged imagery generators that allowed to produce fantasies imbued with the aura of reality. Throughout the 20th century, photography, collage and photo-manipulation have accompanied the evolution of both the modern city and architecture, both portraying them and playing with their photographic image, creating fictions conceived in the canvas of the photographic paper. With the advent of the digital era, the possibilities to manipulate images have grown exponentially, taking photography further away from its alleged built-in objectivity, but also multiplying its ability to engender novel, captivating images. ‘Real Fictions’ presents an overview of the architectural imagery that the digital processing of images is producing, from the work of authors with a close relationship with disciplinary architecture such as Philipp Schaerer or Filip Dujardin to the architectural fictions generated by a heterogeneous multitude of artists and professionals, in order to discuss their potential contributions both to the discipline and to the claim for the role of photography in the age of digital image production.
Keywords: Photography; Photomontage; Photo-collage; Fiction; Surrealism